Leveraging airborne imaging spectroscopy and multispectral satellite imagery to map glacial sediment plumes in Kachemak Bay, Alaska - L. Hartl; C. Schmitt; M. Stuefer; J. Jenckes; B. Page; C. Crawford; G. Schmidt; R. Yang; R. Hock (Journal of Hydrology: Regional Studies)
Study RegionKachemak Bay is a fjord-type estuary in the northern Gulf of Alaska. Water quality and habitat characteristics are strongly influenced by freshwater and sediment input from multiple glacierized catchments.Study FocusWe present a new method combining imaging spectroscopy from an airborne survey with Landsat and Sentinel-2 imagery to map water surface turbidity originating from glacial runoff based on spectral abundance. We compare the spectral characteristics of turbid glacial water to clear water and generate a high resolution reference map of glacial turbidity in Kachemak Bay. This informs the subsequent analysis of a homogenized, Rayleigh corrected time series of Landsat and Sentinel-2 images and seasonal patterns of turbidity.New Hydrological Insights for the RegionOur results provide the most comprehensive data set on water surface turbidity in Kachemak Bay to date and improve understanding of spatial and seasonal variability of glacial turbidity in a data sparse region. July and August have the largest plumes with median sizes around 150 km2, or around a quarter of Kachemak Bay. Plume sizes typically decrease with decreasing glacier runoff in September and October. We show that imaging spectroscopy aids assessments of turbid water in glacial marine catchments across scales. Leveraging high resolution spectral information allows for water color analyses that are customized to local conditions and catchment characteristics as well as scalable to wider regions.